Experimental study of the combustion process of gaseous fuels containing nitrogen compounds with the use of new, low-emission Zonal Volumetric Combustion technology. (1st December 2015) - Szewczyk, Dariusz; Jankowski, Radosław; Ślefarski, Rafał; Chmielewski, Jan
Abstract: The article presents the description and the result of the test of the innovative Zonal Volumetric Combustion ( ZVC ) technology, applying several primary methods for the reduction of toxic compounds (mainly NOX, CO and CX HY ) produced during the combustion of gaseous fuels, also those of a low calorific value like syngas, biogas, and waste gas of a different chemical composition, in industrial combustion systems. The experimental studies included the influence of nitrogenous compounds (NH3 ) in the fuels on the total emission of NOX and CO. The ZVC technology was designed and developed by the ICS Company. It has been shown that the best conversion factor (CF), which describes the amount of NOX produced relative to the amount of nitrogen compounds in the fuel, was obtained for the case where in the reducing zone oxygen was at a very low level. Even with such a small amount of oxygen in the reducing zone of the combustion chamber, the measured CO emission was less than 5 ppm. The application of the above combustion technology in new and retrofit, large and medium combustion plants allows achieving the emission levels of toxic compounds lower than those resulting from the IED [12] and BAT conclusions [5]. Highlights: The Zonal Volumetric Combustion (ZVC) technology is tested and described. Low NOX emission and CO emission was achieved with high O2 concentration. The conversion factor was determined to calculate the expected NOX emission value. High reduction factor of fuels NOx was received. Low emission ZVC with high O2 in exhaust content was obtain for all fuels.